Composition for electrode, capacitive deionization electrode, and application

CN120039980BActive Publication Date: 2026-10-30FOSHAN SHUNDE MIDEA WATER DISPENSER MFG +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411061024.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2026-10-30
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

目前,活性炭在电容去离子技术上展现了较好去离子性能,但在将活性炭商业化应用过程中存在如下问题:(1)虽然活性炭的比表面积大,但是其孔径分布以微孔(<2 nm)为主,对于水合离子的传质及扩散具有一定的限制作用,同时因活性炭本身的亲水性较差导致其在电容去离子中的应用受到限制;(2)活性炭本身的导电性不高,电阻较高,在电极制备过程中需要添加导电性差的聚合物粘结剂,因此,活性炭类电极材料的导电性普遍较差

Benefits of technology

[0037]本发明关于电容去离子电极的技术方案至少具有以下有益效果:本发明中的电容去离子电极具有较高的脱盐速率、较大的比表面积、较高的孔体积和较低的电阻率、较好的使用寿命和使用稳定性;可以实现快速高效的脱除水中的阴阳离子,在电容去离子水处理领域具有较好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120039980B_ABST
    Figure CN120039980B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of electrode composition, capacitive deionization electrode and application, the electrode composition includes porous carbon material, oxidation modified conductive carbon material and binder, the mass ratio of binder, porous carbon material and oxidation modified conductive carbon material is 1 :(4-96):(0.2-15).The present application introduces oxidation modified conductive carbon material with excellent conductive performance in porous carbon material, charge can be quickly transferred in electrode composition, and then improve the desalination rate of capacitive deionization electrode made of electrode composition.Oxidation modified conductive carbon material is connected between porous carbon material by the interaction between functional groups and / or physical entanglement effect, improve the dispersibility of porous carbon material, avoid the agglomeration of porous carbon material, and then reduce the amount of binder, improve the conductive performance of capacitive deionization electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment, specifically to an electrode composition, a capacitive deionization electrode, and their applications. Background Technology

[0002] Capacitive deionization technology typically uses capacitors as the core component of deionization equipment. When water flows through the capacitor, the electric field on the electrodes separates ions with different charges from the water. This technology can remove various ions from water, including sodium, magnesium, calcium, iron, copper, lead, chloride, carbonate, sulfate, and other anions and cations, thereby purifying the water. Capacitive deionization technology has advantages such as high efficiency, energy saving, and environmental friendliness, and has broad application prospects in water treatment (including seawater and brackish water desalination, lithium extraction from salt lakes, drinking water purification, and water softening).

[0003] The capacitors used in capacitive deionization technology are also known as supercapacitors. Supercapacitors differ from ordinary capacitors in specific surface area and charge storage method. Compared to ordinary capacitors, whose capacitance is usually only a few microfarads or millifarads, supercapacitors can have capacitances of hundreds or even thousands of farads.

[0004] The key to capacitive deionization technology lies in the electrode material of supercapacitors. Currently, activated carbon has shown good deionization performance in capacitive deionization technology, but there are the following problems in the process of commercial application of activated carbon: (1) Although activated carbon has a large specific surface area, its pore size distribution is mainly micropores (<2 nm), which has a certain limiting effect on the mass transfer and diffusion of hydrated ions. At the same time, the poor hydrophilicity of activated carbon itself limits its application in capacitive deionization; (2) Activated carbon itself has low conductivity and high resistance. In the electrode preparation process, it is necessary to add polymer binders with poor conductivity. Therefore, the conductivity of activated carbon electrode materials is generally poor. Summary of the Invention

[0005] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, one object of the present invention is to provide an electrode composition.

[0006] A second objective of this invention is to provide a method for preparing the above-mentioned electrode composition.

[0007] The third objective of this invention is to provide a capacitive deionization electrode.

[0008] The fourth objective of this invention is to provide a water treatment device.

[0009] The fifth objective of this invention is to provide the application of the above-mentioned electrode composition and / or capacitive deionization electrode in the field of water treatment.

[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides an electrode composition comprising a porous carbon material, an oxidized conductive carbon material, and a binder, wherein the mass ratio of the binder, the porous carbon material, and the oxidized conductive carbon material is 1:(4~96):(0.2~15).

[0011] The technical solution of the electrode composition of the present invention has at least the following beneficial effects: Introducing an oxidized conductive carbon material with excellent conductivity into a porous carbon material can improve the overall conductivity of the electrode composition, allowing for rapid charge transfer in the electrode prepared from this composition, thereby increasing the desalination rate of the electrode. The oxidized conductive carbon material contains oxygen-containing functional groups, which can connect with the porous carbon material through interactions and / or physical entanglement between functional groups, improving the dispersibility of the porous carbon material and preventing agglomeration caused by electrostatic effects. Furthermore, it can reduce the amount of binder used during electrode preparation, minimizing the impact of non-conductive binders on the conductivity of the electrode composition.

[0012] According to some embodiments of the present invention, the mass ratio of the binder, porous carbon material, and oxidized conductive carbon material is 1:(5~96):(0.2~15), for example: it can be 1:5:0.2, 1:5:5, 1:5:15, 1:6:0.2, 1:6:8, 1:6:15, 1:8:0.8, 1:8:1.2, 1:8:2, 1:8:5, 1:8:15, 1:9:0.8, 1:9:0.9, 1:9:1, 1:9:1.2, 1:10:0.2, 1:10:0.8, 1:10:0.9, 1:10:1, 1:10:1.5, 1:10: 2, 1:10:2.5, 1:11:0.8, 1:11:0.9, 1:11:1, 1:11:1.2, 1:11:1.8, 1:11:2, 1:11:2.5, 1:12:0.8, 1:12:1.4, 1:12:1.9, 1:12:2.5, 1:13:0.8, 1:13:0.9, 1:13:1, 1:13:1.2, 1:13:1.8, 1:13:2, 1:13:2.5, 1:14:0.8, 1:14:0.9, 1:14:1, 1:14:1.2, 1:14:1.8, 1:14:2, 1:14: 2.5, 1:15:0.2, 1:15:10, 1:15:15, 1:16:0.8, 1:16:0.9, 1:16:1, 1:16:1.2, 1:16:1.8, 1:16:3, 1:16:5, 1:20:0.2, 1:20:6, 1:20:15, 1:30:0.2, 1:30:5, 1:30:15, 1:40:0.2, 1:40:13, 1:50:0.2, 1:50:11, 1:60:0.2, 1:60:15, 1:70:0.2, 1:70:5, 1:70:15, 1:80:5, 1:80 :10, 1:90:5, 1:90:15, 1:96:5, 1:96:10, 1:96:15; According to some embodiments of the present invention, the mass ratio of the binder, the porous carbon material and the oxidized conductive carbon material is 1:(5~50):(0.5~8); According to some embodiments of the present invention, the mass ratio of the binder, the porous carbon material and the oxidized conductive carbon material is 1:(5~35):(0.5~5); According to some embodiments of the present invention, the mass ratio of the binder, the porous carbon material and the oxidized conductive carbon material is 1:(10~16):(0.8~2.5).

[0013] In this invention, the mass ratio of binder, porous carbon material, and oxidized conductive carbon material must meet the above-mentioned range. Since binder is generally a non-conductive material, a high amount of binder will affect the conductivity of the electrode composition. A low amount of binder will easily cause the oxidized conductive carbon material and porous carbon material to detach during electrode preparation, affecting the electrode's lifespan and desalination rate. A low amount of oxidized conductive carbon material will only slightly improve conductivity, while a high amount will affect the desalination effect. A high amount of porous carbon material will result in poor dispersibility and agglomeration, which is detrimental to obtaining a uniform electrode composition. A low amount of porous carbon material will also affect the desalination effect.

[0014] In this invention, the mass ratio of binder to porous carbon material and the mass ratio of binder to oxidized conductive carbon material must meet the above-mentioned ranges. Since binders are generally non-conductive materials, a high amount of binder will affect the conductivity of the electrode composition. A low amount of binder will easily cause the oxidized conductive carbon material and porous carbon material to detach during electrode preparation, affecting the electrode's lifespan and desalination rate. A low amount of oxidized conductive carbon material will only slightly improve conductivity, while a high amount will affect the desalination effect. A high amount of porous carbon material will result in poor dispersion and agglomeration, which is detrimental to obtaining a uniform electrode composition. A low amount of porous carbon material will also affect the desalination effect.

[0015] According to some embodiments of the present invention, at least a portion of the porous carbon material and the oxidized conductive carbon material are connected by hydrogen bonds and / or physical entanglement in the electrode composition. In the electrode composition of the present invention, the oxidized conductive carbon material contains oxygen-containing functional groups, and the surface of the porous carbon material also contains some oxygen-containing functional groups. Hydrogen bonds are formed between a portion of the porous carbon material and the oxygen-containing functional groups in the oxidized conductive carbon material, connecting them together through hydrogen bonding. And / or, a portion of the porous carbon material and the oxidized conductive carbon material are physically entangled, dispersed through hydrogen bonds and / or physical entanglement, improving the dispersibility of the porous carbon material and avoiding agglomeration caused by electrostatic effects. This also reduces the amount of binder used during electrode preparation, minimizing the impact of non-conductive binders on the conductivity of the electrode composition.

[0016] According to some embodiments of the present invention, the porous carbon material is selected from activated carbon, oxidized activated carbon, or a combination thereof; according to some embodiments of the present invention, the porous carbon material is oxidized activated carbon. When the porous carbon material is oxidized activated carbon, the amount of oxygen-containing functional groups in the porous carbon material is relatively high, which can form more hydrogen bonds with the oxidized conductive carbon material. Compared with activated carbon, oxidized activated carbon has a better dispersion effect and a better effect in reducing the amount of binder used. In addition, oxidized activated carbon has a better hydrophilic effect than activated carbon, making it more suitable for use in the field of water treatment.

[0017] According to some embodiments of the present invention, the porous carbon material is oxidized activated carbon, wherein the mass percentage of oxygen in the oxidized activated carbon is 1-10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%; according to some embodiments of the present invention, the porous carbon material is oxidized activated carbon, wherein the mass percentage of oxygen in the oxidized activated carbon is 2-8%; according to some embodiments of the present invention, the porous carbon material is oxidized activated carbon, wherein the mass percentage of oxygen in the oxidized activated carbon is 4-7%. If the oxygen content in the oxidized activated carbon is too high (e.g., greater than 10%), it will affect the conductivity of the electrode. If the oxygen content in the oxidized activated carbon is low (e.g., less than 1%), the dispersibility of the oxidized activated carbon will decrease and the amount of binder used will be relatively high.

[0018] According to some embodiments of the present invention, the mass percentage of oxygen in the oxidized conductive carbon material is 1-30%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%. According to some embodiments of the present invention, the mass percentage of oxygen in the oxidized conductive carbon material is 1-15%. According to some embodiments of the present invention, the mass percentage of oxygen in the oxidized conductive carbon material is 1-10%. According to some embodiments of the present invention, the mass percentage of oxygen in the oxidized conductive carbon material is 2-8%. If the oxygen content in the oxidized conductive carbon material is too high (e.g., greater than 30%), it will affect the conductivity of the electrode. If the oxygen content in the oxidized conductive carbon material is low (e.g., less than 1%), the dispersibility of the oxidized activated carbon will decrease and the amount of binder used will be relatively high.

[0019] According to some embodiments of the present invention, the conductive carbon material is selected from at least one of graphene, carbon nanotubes, conductive carbon black, and carbon fiber. Introducing the above-mentioned conductive carbon material into the electrode composition of the present invention can further improve conductivity, and the oxidation modification imparts oxygen-containing functional groups to the surface of the conductive carbon material, enabling the formation of hydrogen bonds with the porous carbon material, thereby improving the dispersion effect of the porous carbon material and reducing the amount of binder used.

[0020] According to some embodiments of the present invention, the porous carbon material is granular; the conductive carbon material is selected from carbon nanotubes, carbon fibers, or combinations thereof. When the porous carbon material is granular and the conductive carbon material is non-granular (i.e., carbon nanotubes, carbon fibers, or combinations thereof), it facilitates the physical entanglement between the non-granular conductive carbon material and the granular porous carbon material, which is beneficial for constructing a connected conductive network, thereby improving the dispersibility of the porous carbon material while reducing the amount of binder used.

[0021] According to some embodiments of the present invention, the electrode composition further includes a solvent. The solvent serves to disperse the binder, porous carbon material, and oxidized conductive carbon material, which facilitates the processing of the electrode composition into an electrode and improves the processing performance of the electrode composition.

[0022] According to some embodiments of the present invention, the mass percentage of the solvent is 60-95% when the electrode composition is 100% by mass, for example, it can be: 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%. According to some embodiments of the present invention, the mass percentage of the solvent is 60-80% when the electrode composition is 100% by mass. If the amount of solvent is too large, the solid content of the electrode composition is too low, which is not conducive to the processing and fabrication of the electrode; if the amount of solvent is too small, the solid content of the electrode composition is too high, which is not conducive to obtaining an electrode film with good thickness uniformity.

[0023] According to some embodiments of the present invention, the solvent is selected from at least one of methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, carbon tetrachloride, N-methylpyrrolidone, and water. The solvents used in the present invention have less environmental pollution, higher safety, lower cost, and are easily volatile, which is beneficial for obtaining electrode films with high thickness uniformity.

[0024] According to some embodiments of the present invention, the binder is selected from at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyamic acid, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, carboxymethyl cellulose, sodium carboxymethyl cellulose, and styrene-butadiene rubber. Compared with other binders in the prior art, the binder of the present invention has less impact on the conductivity of the electrode composition during use and has better compatibility with porous carbon materials and oxidized conductive carbon materials.

[0025] According to some embodiments of the present invention, the weight-average molecular weight of the adhesive is 5,000 to 2,000,000, for example, it can be: 5,000, 7,000, 9,000, 10,000, 12,000, 14,000, 16,000, 18,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 100,000, 20,000. 0, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1000,000, 1100,000, 1200,000, 1300,000, 1400,000, 1500,000, 1600,000, 1700,000, 1800,000, 1900,000, 2000,000. When the weight-average molecular weight of the binder is too low, for example below 5,000, the binder has low viscosity and poor adhesion. When the weight-average molecular weight of the binder is too high, for example above 2,000,000, the binder has excessive viscosity, which is not conducive to the dispersion of porous carbon materials and oxidized conductive carbon materials.

[0026] The second aspect of the present invention provides a method for preparing the electrode composition provided in the first aspect of the present invention, comprising the following steps: mixing the oxidized conductive carbon material, the porous carbon material, the binder, and optionally added solvent to obtain the composition.

[0027] The technical solution of the present invention regarding the preparation method of electrode composition has at least the following beneficial effects: The present invention uses oxidized conductive carbon material, porous carbon material and binder as raw materials, which are widely available and inexpensive. At the same time, the preparation method of the present invention is to obtain the material by physically mixing the raw materials evenly. The preparation method is simple, the reaction conditions are mild, no equipment is required, and it can be mass-produced industrially.

[0028] According to some embodiments of the present invention, the preparation method includes the following steps: S1: The binder is mixed with a portion of the solvent to obtain a binder dispersion; the oxidized conductive carbon material, the porous carbon material, and the remaining solvent are mixed to obtain a conductive dispersion; S2: The electrode composition is prepared by mixing the binder dispersion and the conductive dispersion.

[0029] The present invention involves first preparing a binder dispersion and a conductive dispersion separately, and then mixing the two together. This preparation method is beneficial for the mixing and dispersion of the binder, the oxidized conductive carbon material and the porous carbon material, thereby avoiding the aggregation of the porous carbon material due to electrostatic interaction.

[0030] According to some embodiments of the present invention, the mixing step in the preparation method is carried out at a temperature of 15-40°C, for example, at 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 37°C, 38°C, 39°C, or 40°C; according to some embodiments of the present invention, the mixing step in the preparation method is carried out at a temperature of 20-35°C. The present invention uses a lower mixing temperature, which can save energy and reduce costs.

[0031] According to some embodiments of the present invention, in the preparation method, the mixing time is 1 to 10 hours, for example, the mixing time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours. The present invention uses a mixing time of 1 to 10 hours to ensure uniform mixing of the raw materials and good dispersion of the porous carbon material and the oxidized conductive carbon material.

[0032] According to some embodiments of the present invention, the mixing step is performed by stirring. The present invention uses stirring for mixing, which requires less equipment and can reduce production costs.

[0033] According to some embodiments of the present invention, the stirring rate is 100~10000 rpm, for example, it can be 100 rpm, 200 rpm, 400 rpm, 500 rpm, 600 rpm, 800 rpm, 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, or 10000 rpm; according to some embodiments of the present invention, the stirring rate is 500~5000 rpm; according to some embodiments of the present invention, the stirring rate is 500~2000 rpm. Stirring and mixing at a stirring rate of 100~10000 rpm can fully disperse the porous carbon material and the oxide-modified conductive carbon material.

[0034] According to some embodiments of the present invention, step S2 specifically involves: mixing the binder dispersion and the conductive dispersion, and then sieving them to obtain the electrode composition. The sieving step can prevent the electrode composition from containing large particles, which would affect subsequent use, and is beneficial for obtaining an electrode film with good thickness and compositional uniformity.

[0035] According to some embodiments of the present invention, the sieving step involves filtering with a 50-500 mesh sieve. If the mesh size is too small, the particles in the electrode composition are too small, which is detrimental to constructing a conductive network and achieving the objectives of the present invention, and affects the conductivity of the electrode composition. If the mesh size is too large, the electrode composition contains large particles of raw material, which is detrimental to obtaining an electrode membrane with good thickness and compositional uniformity.

[0036] A third aspect of the present invention provides a capacitive deionization electrode, comprising an electrode layer; the electrode layer is prepared from an electrode composition provided in the first aspect of the present invention.

[0037] The technical solution of the capacitive deionization electrode of the present invention has at least the following beneficial effects: the capacitive deionization electrode of the present invention has a high desalination rate, a large specific surface area, a high pore volume and a low resistivity, a good service life and stable operation; it can achieve rapid and efficient removal of anions and cations from water, and has good application prospects in the field of capacitive deionization water treatment.

[0038] According to some embodiments of the present invention, the maximum adsorption rate of anions and cations of the capacitive deionization electrode is 200~400 mg / (m²). 2 (·min), for example, can be: 200 mg / (m 2 ·min), 210 mg / (m 2 ·min), 220 mg / (m 2 ·min), 230 mg / (m 2 ·min), 240 mg / (m 2 ·min), 250 mg / (m 2 ·min), 260 mg / (m 2 ·min), 270 mg / (m 2 ·min), 280 mg / (m 2 ·min), 290 mg / (m 2 ·min), 300 mg / (m 2 ·min), 310 mg / (m 2 ·min), 320 mg / (m 2 ·min), 330 mg / (m 2·min), 340 mg / (m 2 ·min), 350 mg / (m 2 ·min), 360 mg / (m 2 ·min), 370 mg / (m 2 ·min), 380 mg / (m 2 ·min), 390 mg / (m 2 ·min), 400 mg / (m 2 According to some embodiments of the present invention, the maximum adsorption rate of anions and cations of the capacitive deionization electrode is 240~350 mg / (m). 2 According to some embodiments of the present invention, the maximum adsorption rate of anions and cations of the capacitive deionization electrode is 240~330 mg / (m). 2 (min). The capacitive deionization electrode in this invention has a large adsorption rate, which is beneficial for quickly adsorbing and removing positive and negative ions from water.

[0039] According to some embodiments of the present invention, the specific surface area of ​​the capacitive deionization electrode is 700~2500 m². 2 / g, for example, could be: 700 m 2 / g、800 m 2 / g、900 m 2 / g, 1000 m 2 / g、1100 m 2 / g、1200 m 2 / g、1300 m 2 / g、1400 m 2 / g, 1500 m 2 / g、1600 m 2 / g、1700 m 2 / g、1800 m 2 / g、1900 m 2 / g、2000 m 2 / g、2100 m 2 / g、2200 m 2 / g、2300 m 2 / g、2400 m 2 / g、2500 m 2 / g. The capacitive deionization electrode in this invention has a large specific surface area, which is beneficial for obtaining a high desalination rate.

[0040] According to some embodiments of the present invention, the pore volume of the capacitive deionization electrode is 0.8~1.1 cm³. 3 / g, for example, can be 0.8 cm 3 / g, 0.85 cm 3 / g, 0.9 cm 3 / g, 0.95 cm 3 / g, 1.0 cm 3 / g, 1.05 cm 3 / g, 1.1cm 3 / g; The capacitive deionization electrode in this invention has an appropriate pore volume, which is beneficial for the adsorption and deintercalation of positive and negative ions in water.

[0041] According to some embodiments of the present invention, the resistivity of the capacitive deionization electrode is 0.3~0.7 Ω·cm, for example, it can be 0.3 Ω·cm, 0.35 Ω·cm, 0.4 Ω·cm, 0.45 Ω·cm, 0.5 Ω·cm, 0.55 Ω·cm, 0.6 Ω·cm, 0.65 Ω·cm, or 0.7 Ω·cm. The capacitive deionization electrode of the present invention has low resistivity and excellent conductivity.

[0042] According to some embodiments of the present invention, the desalination rate of the capacitive deionization electrode is not less than 60% when the operating voltage is 1.5~2V. For example, the desalination rate can be 61%, 63%, 65%, 67%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, or 100%. The capacitive deionization electrode of the present invention has a high desalination rate over a wide voltage range.

[0043] According to some embodiments of the present invention, the pore size of the pore in the capacitor deionization electrode is on the micrometer scale.

[0044] A fourth aspect of the present invention provides a water treatment device including the capacitive deionization electrode described in the third aspect of the present invention.

[0045] According to some embodiments of the present invention, the water treatment equipment includes water purification equipment, water desalination equipment, and water softening equipment.

[0046] The fifth aspect of the present invention provides the application of the electrode composition provided in the first aspect of the present invention and / or the capacitive deionization electrode provided in the third aspect of the present invention in the field of water treatment.

[0047] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description

[0048] Figure 1This is a surface morphology diagram of the capacitor deionization electrode in Example 8.

[0049] Figure 2 This is a test graph showing the desalination performance and voltage relationship curve of the capacitive deionization electrode in Example 8.

[0050] Figure 3 This is a test graph showing the desalination performance and voltage relationship curve of the capacitive deionization electrode in Example 9. Detailed Implementation

[0051] The specific implementation of the present invention will be further described in detail below with reference to the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that any processes not specifically described in detail below are those that can be implemented or understood by those skilled in the art by referring to the prior art. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.

[0052] In developing compositions for capacitive deionization electrodes, the inventors attempted to address the problems of poor hydrophilicity and micropore size of activated carbon, which negatively impacted the mass transfer and diffusion of hydrated ions, resulting in poor deionization efficiency and effectiveness. Various methods, including strong alkali heat treatment, template methods, and chemical vapor deposition, were tried to fabricate porous carbon material electrodes. While these methods improved the specific surface area, pore size, and hydrophilicity of the porous carbon material electrodes, they still could not meet the requirements for rapid and efficient adsorption of anions and cations in water. Furthermore, the porous carbon materials prepared by these methods all contained certain defects. These defects could improve the hydrophilicity of the porous carbon materials, but they also reduced their conductivity to some extent. Therefore, the inventors continued their research on porous carbon material electrodes, attempting to treat the porous carbon materials at high temperatures to reduce surface defects. This improved the conductivity of the porous carbon materials to some extent, but it still could not meet the application requirements. In addition, strong alkali heat treatment, template methods, chemical vapor deposition, and high-temperature treatment methods all suffered from cumbersome processes, high costs, poor repeatability, and were unsuitable for large-scale industrial production.

[0053] The inventors continued their research and development on porous carbon material electrodes, attempting to introduce conductive carbon materials into porous carbon materials. The inventors discovered that a large amount of non-conductive binder needed to be added during electrode preparation, resulting in high resistivity and poor conductivity of the electrode. Furthermore, conductive carbon materials and porous carbon materials are different materials, leading to a large amount of agglomeration of porous carbon materials during electrode preparation, resulting in poor dispersion and failing to meet the requirements for use as capacitive deionization electrodes.

[0054] The inventors continued their research and development on compositions for capacitive deionization electrodes, introducing oxidized conductive carbon materials and porous carbon materials. Partial hydrogen bonds form between the oxidized conductive carbon materials and porous carbon materials, connecting them and preventing the agglomeration of the porous carbon materials. Secondly, physical entanglement exists between carbon nanotubes and / or oxidized carbon fibers and the particulate porous carbon materials, further binding the oxidized conductive carbon materials and porous carbon materials together. This reduces the amount of binder used during electrode fabrication, minimizing the impact of binder on the electrode's conductivity. Furthermore, the introduction of oxidized conductive carbon materials also reduces the electrode's resistivity and improves its conductivity.

[0055] To further improve desalination efficiency and adsorption rate, the inventors experimented with electrodes made of oxidized conductive carbon materials and oxidized activated carbon. These electrodes possess high specific surface area, large pore volume, and large pore size, enabling rapid mass transfer and diffusion of hydrated ions, thereby increasing the adsorption rate of anions and cations in water. This resulted in a maximum adsorption rate of 200–400 mg / (m³). 2 (min). In addition, both oxidized conductive carbon materials and oxidized activated carbon have good hydrophilic properties, which can meet the material performance requirements of capacitive deionization electrodes in the water treatment field.

[0056] In some embodiments of the present invention, an electrode composition is provided, comprising a porous carbon material, an oxidized conductive carbon material, and a binder, wherein the mass ratio of the binder, the porous carbon material, and the oxidized conductive carbon material is 1:(4~96):(0.2~15).

[0057] In some embodiments of the present invention, the porous carbon material and the oxidized conductive carbon material are connected by hydrogen bonds. The oxidized conductive carbon material contains oxygen-containing functional groups, and the surface of the porous carbon material also contains some oxygen-containing functional groups. The porous carbon material and the oxidized conductive carbon material can be connected by hydrogen bonds, and there is also physical entanglement between them. Through hydrogen bonding and physical entanglement, the dispersibility of the porous carbon material is improved, and the agglomeration of particulate porous carbon material due to electrostatic effects is avoided.

[0058] In some embodiments of the present invention, the mass ratio of the binder, porous carbon material, and oxidized conductive carbon material is 1:(5~96):(0.2~15), for example: 1:5:0.2, 1:5:5, 1:5:15, 1:6:0.2, 1:6:8, 1:6:15, 1:8:0.8, 1:8:1.2, 1:8:2, 1:8:5, 1:8:15, 1:9:0.8, 1:9:0.9, 1:9:1, 1:9:1.2, 1:10:0.2, 1:10:0.8, 1:10:0.9, 1:10:1, 1:10:1.5, 1:10 :2, 1:10:2.5, 1:11:0.8, 1:11:0.9, 1:11:1, 1:11:1.2, 1:11:1.8, 1:11:2, 1:11:2.5, 1:12:0.8, 1:12:1.4, 1:12:1.9, 1:12:2.5, 1:13:0.8, 1:13:0.9, 1:13:1, 1:13:1.2, 1:13:1.8, 1:13:2, 1:13:2.5, 1:14:0.8, 1:14:0.9, 1:14:1, 1:14:1.2, 1:14:1.8, 1:14:2 1:14:2.5, 1:15:0.2, 1:15:10, 1:15:15, 1:16:0.8, 1:16:0.9, 1:16:1, 1:16:1.2, 1:16:1.8, 1:16:3, 1:16:5, 1:20:0.2, 1:20:6, 1:20:15, 1:30:0.2, 1:30:5, 1:30:15, 1:40:0.2, 1:40:13, 1:50:0.2, 1:50:11, 1:60:0.2, 1:60:15, 1:70:0.2, 1:70:5, 1:70:15, 1: 80:5, 1:80:10, 1:90:5, 1:90:15, 1:96:5, 1:96:10, 1:96:15; In some embodiments of the present invention, the mass ratio of binder, porous carbon material and oxidized conductive carbon material is 1:(5~50):(0.5~8); In some embodiments of the present invention, the mass ratio of binder, porous carbon material and oxidized conductive carbon material is 1:(5~35):(0.5~5); In some embodiments of the present invention, the mass ratio of binder, porous carbon material and oxidized conductive carbon material is 1:(10~16):(0.8~2.5).

[0059] In this invention, the mass ratio of binder, porous carbon material, and oxidized conductive carbon material must meet the above-mentioned range. Since binder is generally a non-conductive material, a high amount of binder will affect the conductivity of the electrode composition. A low amount of binder will easily cause the oxidized conductive carbon material and porous carbon material to detach during electrode preparation, affecting the electrode's lifespan and desalination rate. A low amount of oxidized conductive carbon material will only slightly improve conductivity, while a high amount will affect the desalination effect. A high amount of porous carbon material will result in poor dispersibility and agglomeration, which is detrimental to obtaining a uniform electrode composition. A low amount of porous carbon material will also affect the desalination effect.

[0060] In some embodiments of the present invention, at least a portion of the porous carbon material and the oxidized conductive carbon material are connected by hydrogen bonds in the electrode composition. In the electrode composition of the present invention, the oxidized conductive carbon material contains oxygen-containing functional groups, and the surface of the porous carbon material also contains some oxygen-containing functional groups. Hydrogen bonds are formed between a portion of the porous carbon material and the oxygen-containing functional groups in the oxidized conductive carbon material, connecting them together through hydrogen bonding. The remaining porous carbon materials are dispersed through physical mixing such as entanglement, improving the dispersibility of the porous carbon materials and avoiding agglomeration caused by electrostatic interactions. This also reduces the amount of binder used during electrode preparation, minimizing the impact of non-conductive binders on the conductivity of the electrode composition.

[0061] In some embodiments of the present invention, the porous carbon material is selected from activated carbon, oxidized activated carbon, or a combination thereof; in some embodiments of the present invention, the porous carbon material is oxidized activated carbon. When the porous carbon material is activated carbon, the surface of the activated carbon has certain oxygen-containing functional groups, which can form a certain amount of hydrogen bonds with the oxidized conductive carbon material. Furthermore, the porous carbon material has a high specific surface area (specific surface area greater than 1000 m²). 2 / g), with a large number of pores (pore volume greater than 0.57cm³). 3 During desalination, positive and negative ions can be adsorbed in porous carbon materials, and the large specific surface area and large pore volume are beneficial to improving the desalination rate. When the porous carbon material is oxidized activated carbon, the amount of oxygen-containing functional groups in the porous carbon material is relatively high, which can form more hydrogen bonds with the oxidized conductive carbon material. Compared with activated carbon, oxidized activated carbon has better dispersion effect and can reduce the amount of binder used. In addition, oxidized activated carbon has a better hydrophilic effect than activated carbon, making it more suitable for water treatment.

[0062] In some embodiments of the present invention, the oxidized activated carbon is prepared by reacting activated carbon with an oxidant. In some embodiments of the present invention, the oxidant is selected from at least one of concentrated nitric acid, concentrated sulfuric acid, hydrogen peroxide, potassium dichromate, potassium permanganate, and nickel permanganate. By placing the activated carbon in a solution of the oxidant to undergo an oxidation reaction, oxygen-containing functional groups such as carboxyl and hydroxyl groups are introduced into the activated carbon, resulting in good oxidation effect and minimal damage to the activated carbon. This enhances the bonding force between the activated carbon and the oxidized conductive carbon material. Furthermore, the introduction of oxygen-containing functional groups can also improve the hydrophilicity of the activated carbon.

[0063] In some embodiments of the present invention, the porous carbon material is oxidized activated carbon, and the mass percentage of oxygen in the oxidized activated carbon is 1-10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%. In some embodiments of the present invention, the porous carbon material is oxidized activated carbon, and the mass percentage of oxygen in the oxidized activated carbon is 2-8%. In some embodiments of the present invention, the porous carbon material is oxidized activated carbon, and the mass percentage of oxygen in the oxidized activated carbon is 4-7%. If the oxygen content in the oxidized activated carbon is too high (e.g., greater than 10%), it will affect the conductivity of the electrode. If the oxygen content in the oxidized activated carbon is low (e.g., less than 1%), the dispersibility of the oxidized activated carbon will decrease and the amount of binder used will be relatively high.

[0064] In some embodiments of the present invention, the water contact angle of the oxidized activated carbon is 35° to 87°. The oxidized activated carbon of the present invention has excellent hydrophilicity and can be used to remove positive and negative ions from water.

[0065] In some embodiments of the present invention, the mass percentage of oxygen in the oxidized conductive carbon material is 1-30%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%. In some embodiments of the present invention, the mass percentage of oxygen in the oxidized conductive carbon material is 1-15%. In some embodiments of the present invention, the mass percentage of oxygen in the oxidized conductive carbon material is 1-10%. In some embodiments of the present invention, the mass percentage of oxygen in the oxidized conductive carbon material is 2-8%. If the oxygen content in the oxidized conductive carbon material is too high (e.g., greater than 30%), it will affect the conductivity of the electrode. If the oxygen content in the oxidized conductive carbon material is low (e.g., less than 1%), the dispersibility of the oxidized activated carbon will decrease and the amount of binder used will be relatively high.

[0066] In this invention, the mass percentage of oxygen in the oxidized conductive carbon material can be the same as or different from the mass percentage of oxygen in the oxidized activated carbon. When the mass percentage of oxygen in the oxidized activated carbon is 1-10% and the mass percentage of oxygen in the oxidized conductive carbon material is 1-30%, more hydrogen bonds can be formed between the oxidized conductive carbon material and the oxidized activated carbon, which is beneficial to their dispersion and can reduce the amount of binder used. When the mass percentage of oxygen in the oxidized activated carbon is higher, the hydrophilicity is better.

[0067] In some embodiments of the present invention, the conductive carbon material is selected from at least one of graphene, carbon nanotubes, conductive carbon black, and carbon fiber. Introducing the above-mentioned conductive carbon material into the electrode composition of the present invention can further improve conductivity. Furthermore, by oxidative modification, the surface of the conductive carbon material is endowed with oxygen-containing functional groups, which can form hydrogen bonds with the porous carbon material, improving the dispersion effect of the porous carbon material and reducing the amount of binder used.

[0068] In some embodiments of the present invention, the oxidized conductive carbon material is prepared by reacting a conductive carbon material with an oxidant. In some embodiments of the present invention, the oxidant is selected from at least one of concentrated nitric acid, concentrated sulfuric acid, hydrogen peroxide, potassium dichromate, potassium permanganate, and nickel permanganate. By placing the conductive carbon material in a solution of the oxidant to undergo an oxidation reaction, oxygen-containing functional groups such as carboxyl and hydroxyl groups are introduced into the conductive carbon material, resulting in good oxidation effect and minimal damage to the conductive carbon material, thereby enhancing the bonding force between the conductive carbon material and the porous carbon material.

[0069] In some embodiments of the present invention, the conductivity of the oxidized conductive carbon material is 0.21~0.59 Ω·cm. The oxidized conductive carbon material of the present invention has high conductivity, and its introduction into the electrode composition of the present invention can significantly improve conductivity.

[0070] In some embodiments of the present invention, the aspect ratio of the carbon fiber is 2-30; in some embodiments of the present invention, the aspect ratio of the carbon nanotube is 2000-10000. Selecting carbon fibers and carbon nanotubes with the above-mentioned aspect ratios is beneficial for the physical entanglement between the oxidized conductive carbon material and the porous carbon material, and facilitates the construction of a connected conductive network, thereby improving the dispersibility of the porous carbon material while reducing the amount of binder used.

[0071] In some embodiments of the present invention, the porous carbon material is granular; the conductive carbon material is selected from carbon nanotubes, carbon fibers, or combinations thereof. When the porous carbon material is granular and the conductive carbon material is non-granular (i.e., carbon nanotubes, carbon fibers, or combinations thereof), it facilitates the physical entanglement between the non-granular conductive carbon material and the granular porous carbon material, and facilitates the construction of a connected conductive network, thereby improving the dispersibility of the porous carbon material while reducing the amount of binder used.

[0072] In some embodiments of the present invention, the particle size of the porous carbon material is 25~270 μm. The uniform particle size of the porous carbon material in the present invention is beneficial for the dispersion of the porous carbon material when applied in the electrode composition of the present invention.

[0073] In some embodiments of the present invention, the electrode composition further includes a solvent. The role of the solvent is to disperse the binder, porous carbon material, and oxidized conductive carbon material, which facilitates the processing of the electrode composition into an electrode and improves the processing performance of the electrode composition.

[0074] In some embodiments of the present invention, the mass percentage of the solvent is 60-95% based on 100% of the electrode composition. For example, it can be: 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%. In some embodiments of the present invention, the mass percentage of the solvent is 60-80% based on 100% of the electrode composition. If the amount of solvent is too large, the solid content of the electrode composition is too low, which is not conducive to the processing and fabrication of the electrode; if the amount of solvent is too small, the solid content of the electrode composition is too high, which is not conducive to obtaining an electrode film with good thickness uniformity.

[0075] In some embodiments of the present invention, the solvent is selected from at least one of methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, carbon tetrachloride, N-methylpyrrolidone, and water. In some embodiments of the present invention, the solvent is selected from at least one of N-methylpyrrolidone and water. The solvents used in the present invention have less environmental pollution, higher safety, lower cost, and are easily volatile, which is beneficial for obtaining electrode films with high thickness uniformity.

[0076] In some embodiments of the present invention, the binder is selected from at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyamic acid, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, carboxymethyl cellulose, sodium carboxymethyl cellulose, and styrene-butadiene rubber. Compared with other binders in the prior art, the binder of the present invention has less impact on the conductivity of the electrode composition during use and has better compatibility with porous carbon materials and oxidized conductive carbon materials.

[0077] In some embodiments of the present invention, the weight-average molecular weight of the adhesive is 5,000 to 2,000,000, for example, it can be: 5,000, 7,000, 9,000, 10,000, 12,000, 14,000, 16,000, 18,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 100,000, 200,000. 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1000,000, 1100,000, 1200,000, 1300,000, 1400,000, 1500,000, 1600,000, 1700,000, 1800,000, 1900,000, 2000,000. In some embodiments of the present invention, the weight-average molecular weight of the adhesive is 8,000 to 1,000,000. In some embodiments of the present invention, the weight-average molecular weight of the adhesive is 8,000 to 120,000. When the weight-average molecular weight of the binder is too small, for example, below 5000, the binder has low viscosity and cannot play the role of a binder. When the weight-average molecular weight of the binder is too large, for example, above 2000000, the binder has excessive viscosity, which is not conducive to the dispersion of porous carbon materials and oxidized conductive carbon materials, and is even less conducive to obtaining electrode films with high thickness uniformity.

[0078] In some embodiments of the present invention, the present invention also provides a method for preparing the above-mentioned electrode composition, comprising the following steps: mixing an oxidized conductive carbon material, a porous carbon material, a binder, and an optional solvent to obtain the composition.

[0079] This invention uses oxidized conductive carbon materials, porous carbon materials, and binders as raw materials. The raw materials are widely available and inexpensive. At the same time, the preparation method of this invention is to obtain the raw materials by physically mixing them evenly. The preparation method is simple, the reaction conditions are mild, and no equipment is required, so it can be mass-produced industrially.

[0080] In some embodiments of the present invention, the preparation method includes the following steps: S1: Mix the binder with a portion of the solvent to obtain a binder dispersion; mix the oxidized conductive carbon material and porous carbon material with the remaining solvent to obtain a conductive dispersion; S2: The composition for electrodes is prepared by mixing the binder dispersion and the conductive dispersion.

[0081] The present invention involves first preparing a binder dispersion and a conductive dispersion separately, and then mixing the two together. This preparation method is beneficial for the mixing and dispersion of the binder, the oxidized conductive carbon material and the porous carbon material, thereby avoiding the aggregation of the porous carbon material due to electrostatic interaction.

[0082] In some embodiments of the present invention, the mixing step in the preparation method is carried out at a temperature of 15-40°C, for example, at 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 37°C, 38°C, 39°C, or 40°C; in some embodiments of the present invention, the mixing step in the preparation method is carried out at a temperature of 20-35°C. The present invention uses a lower mixing temperature, which can save energy.

[0083] In some embodiments of the present invention, the mixing time in the preparation method is 1 to 10 hours, for example, the mixing time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours. The present invention uses a mixing time of 1 to 10 hours to ensure uniform mixing of the raw materials and good dispersion of the porous carbon material and the oxidized conductive carbon material.

[0084] In some embodiments of the present invention, the mixing step is performed by stirring. The mixing method used in this invention requires less equipment and can reduce production costs.

[0085] In some embodiments of the present invention, the stirring rate is 100~10000 rpm, for example, it can be 100 rpm, 200 rpm, 400 rpm, 500 rpm, 600 rpm, 800 rpm, 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, or 10000 rpm; in some embodiments of the present invention, the stirring rate is 500~5000 rpm; in some embodiments of the present invention, the stirring rate is 500~2000 rpm. Stirring and mixing at a stirring rate of 100~10000 rpm can ensure sufficient dispersion of the porous carbon material and the oxide-modified conductive carbon material.

[0086] In some embodiments of the present invention, step S2 specifically involves mixing the binder dispersion and the conductive dispersion, then sieving them to obtain the electrode composition. The sieving step avoids the presence of large particles in the electrode composition, which could affect subsequent use, and is beneficial for obtaining an electrode film with good thickness and compositional uniformity.

[0087] In some embodiments of the present invention, the sieving step involves filtering with a 50-500 mesh sieve. If the mesh size is too small, the particles in the electrode composition are too small, which is not conducive to building a conductive network and affects the conductivity of the electrode composition. If the mesh size is too large, the electrode composition contains large particles of raw material, which is not conducive to obtaining an electrode film with good thickness and compositional uniformity.

[0088] In some embodiments of the present invention, the present invention also provides a capacitive deionization electrode, comprising an electrode layer; the electrode layer is prepared from the above-mentioned electrode composition.

[0089] The capacitive deionization electrode of this invention has a high desalination rate, a large specific surface area, a high pore volume, a low resistivity, a good service life, and good stability in use; it can achieve rapid and efficient removal of anions and cations from water, and has good application prospects in the field of capacitive deionization water treatment.

[0090] In some embodiments of the present invention, the maximum adsorption rate of anions and cations on the capacitive deionization electrode is 200~400 mg / (m²). 2 (·min), for example, can be: 200 mg / (m 2 ·min), 210 mg / (m 2 ·min), 220 mg / (m 2 ·min), 230 mg / (m 2 ·min), 240 mg / (m 2 ·min), 250 mg / (m 2 ·min), 260 mg / (m 2 ·min), 270mg / (m 2 ·min), 280 mg / (m 2 ·min), 290 mg / (m 2 ·min), 300 mg / (m 2 ·min), 310 mg / (m 2 ·min), 320 mg / (m 2 ·min), 330 mg / (m 2 ·min), 340 mg / (m 2 ·min), 350 mg / (m 2·min), 360mg / (m 2 ·min), 370 mg / (m 2 ·min), 380 mg / (m 2 ·min), 390 mg / (m 2 ·min), 400 mg / (m 2 In some embodiments of the present invention, the maximum adsorption rate of cations and anions on the capacitive deionization electrode is 240~350 mg / (m). 2 In some embodiments of the present invention, the maximum adsorption rate of anions and cations on the capacitive deionization electrode is 240~330 mg / (m). 2 (min). The capacitive deionization electrode in this invention has a large adsorption rate, which is beneficial for quickly adsorbing and removing various positive and negative ions from water.

[0091] In some embodiments of the present invention, the specific surface area of ​​the capacitive deionization electrode is 700~2500 m². 2 / g, for example, could be: 700 m 2 / g、800 m 2 / g、900 m 2 / g, 1000 m 2 / g、1100 m 2 / g、1200 m 2 / g、1300 m 2 / g, 1400m 2 / g, 1500 m 2 / g、1600 m 2 / g、1700 m 2 / g、1800 m 2 / g、1900 m 2 / g、2000 m 2 / g、2100 m 2 / g、2200m 2 / g、2300 m 2 / g、2400 m 2 / g、2500 m 2 / g. In some embodiments of the present invention, the specific surface area of ​​the capacitive deionization electrode is 900~2200 m². 2 / g; In some embodiments of the present invention, the specific surface area of ​​the capacitive deionization electrode is 900~1800m². 2 / g; In some embodiments of the present invention, the specific surface area of ​​the capacitive deionization electrode is 900~1200 m² / g; 2 / g. The capacitive deionization electrode in this invention has a large specific surface area, which is beneficial for obtaining a high desalination rate.

[0092] In some embodiments of the present invention, the pore volume of the capacitive deionization electrode is 0.8~1.1 cm³. 3 / g, for example, can be 0.8 cm 3 / g, 0.85 cm 3 / g, 0.9 cm 3 / g, 0.95 cm 3 / g, 1.0 cm 3 / g, 1.05 cm 3 / g, 1.1 cm 3 / g; The capacitive deionization electrode in this invention has an appropriate pore volume, which is beneficial for the adsorption and deintercalation of positive and negative ions in water.

[0093] In some embodiments of the present invention, the resistivity of the capacitive deionization electrode is 0.3~0.7 Ω·cm, for example, it can be 0.3 Ω·cm, 0.35 Ω·cm, 0.4 Ω·cm, 0.45 Ω·cm, 0.5 Ω·cm, 0.55 Ω·cm, 0.6 Ω·cm, 0.65 Ω·cm, or 0.7 Ω·cm. The capacitive deionization electrode of the present invention has a low resistivity and excellent conductivity.

[0094] In some embodiments of the present invention, the desalination rate of the capacitive deionization electrode at an operating voltage of 1.5~2V is not less than 60%, for example, the desalination rate can be 61%, 63%, 65%, 67%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, or 100%. The capacitive deionization electrode of the present invention has a high desalination rate over a wide voltage range.

[0095] In some embodiments of the present invention, the capacitive deionization electrode contains a microporous structure. The presence of numerous microporous structures in the capacitive deionization electrode of the present invention allows positive and negative ions in water to be adsorbed within the micropores of the capacitive deionization electrode.

[0096] In some embodiments of the present invention, the present invention also provides a water treatment device including the above-described capacitive deionization electrode.

[0097] In some embodiments of the present invention, the water treatment equipment includes water purification equipment, water desalination equipment, and water softening equipment.

[0098] In some embodiments of the present invention, the water treatment device includes two oppositely arranged capacitive deionization electrodes as described above.

[0099] The water treatment equipment of this invention is equipped with the aforementioned capacitive deionizing electrodes. During operation, a DC external voltage is applied to the capacitive deionizing electrodes, thereby creating an electrostatic field between the two electrodes. This causes positive and negative ions in the water to move directionally to the surface of the capacitive deionizing electrode with the opposite charge and be stored there. This reduces the salt concentration in the solution, thus achieving deionization. Reversing the power supply or removing the voltage discharges the capacitive deionizing electrodes, releasing the adsorbed ions back into the solution, regenerating the electrodes. The water treatment equipment of this invention has advantages such as low energy consumption, no secondary pollution, and environmental friendliness, and also exhibits a high desalination rate and desalination efficiency.

[0100] In some embodiments of the present invention, the above-described electrode composition can be used in the field of water treatment.

[0101] In some embodiments of the present invention, the above-described capacitive deionization electrode can be applied in the field of water treatment.

[0102] The implementation of the present invention will be further illustrated in detail below with reference to specific embodiments: The specific preparation method of the oxidized carbon nanotubes used in this embodiment of the invention is as follows: carbon nanotubes and nitric acid solution (nitric acid concentration of 12 mol / L) are placed in a three-necked flask and reacted at a temperature of 80 ℃. Then, the oxidized carbon nanotubes are washed with pure water until the pH value is neutral, and dried to obtain the final product. By changing the ratio of carbon nanotubes to nitric acid and the reaction time, oxidized carbon nanotubes with different oxygen contents can be obtained.

[0103] The oxidized activated carbon used in the embodiments of the present invention has better hydrophilicity after oxidation modification. It can be prepared by oxidizing activated carbon with an oxidant, referring to the preparation method of carbon nanotubes.

[0104] Example 1 This example provides an electrode composition, which is prepared by the following method, including the following steps: Polyvinylidene fluoride and N-methylpyrrolidone were mixed at a mass ratio of 1:20 and dispersed by stirring at 25 °C for 3 hours using a homogenizer at a stirring speed of 1000 rpm to obtain a dispersion of the adhesive material, wherein the weight average molecular weight of polyvinylidene fluoride was 110,000.

[0105] Carbon nanotubes (i.e., oxidized conductive carbon material), oxidized activated carbon (i.e., porous carbon material), and N-methylpyrrolidone were mixed in a mass ratio of 1:10:20 and stirred in a homogenizer at 25 °C for 3 hours at a stirring speed of 1000 rpm. Then, the mixture was mixed with the dispersion of the above binder material and stirred for another 5 hours at a stirring speed of 1000 rpm. The mixed slurry was filtered through a 200-mesh stainless steel mesh to obtain the electrode composition in this example.

[0106] In this example, the electrode composition contains 25% by mass of solids (solids refer to polyvinylidene fluoride, carbon nanotubes, and oxidized activated carbon). Specifically, based on the total mass percentage of solids in the electrode composition being 100%, polyvinylidene fluoride accounts for 6.3% by mass, carbon nanotubes for 8.5% by mass, and oxidized activated carbon for 85.2% by mass. The carbon nanotubes contain 10% oxygen by mass, and the oxidized activated carbon contains 2% oxygen by mass.

[0107] Example 2 This example provides an electrode composition, which is prepared by the following method, including the following steps: Sodium carboxymethyl cellulose was mixed with water at a mass ratio of 1:20 and dispersed by stirring at 25 °C for 3 hours using a homogenizer at a stirring speed of 1000 rpm to obtain a dispersion of the binder material, wherein the weight average molecular weight of sodium carboxymethyl cellulose was 80,000.

[0108] Carbon nanotubes, oxidized activated carbon, and water were mixed in a mass ratio of 1:10:20 and stirred in a homogenizer at 25 °C for 5 hours at a stirring speed of 1000 rpm. The mixture was then mixed with the dispersion of the binder material and stirred for another 10 hours at a stirring speed of 1000 rpm. The mixed slurry was then filtered through a 200-mesh stainless steel mesh to obtain the electrode composition in this example.

[0109] In this example, the electrode composition contains 25% by mass of solids (solids refer to sodium hydroxymethyl cellulose, carbon nanotubes, and oxidized activated carbon). Of this, based on a total solids content of 100%, sodium hydroxymethyl cellulose comprises 6.3%, carbon nanotubes comprise 8.5%, and oxidized activated carbon comprises 85.2%. Specifically, the carbon nanotubes contain 10% oxygen by mass, and the oxidized activated carbon contains 2% oxygen by mass.

[0110] Example 3 This example provides an electrode composition, which is prepared by the following method, including the following steps: Polyvinylidene fluoride and N-methylpyrrolidone were mixed at a mass ratio of 1:20 and dispersed by stirring at 25 °C for 3 hours using a homogenizer at a stirring speed of 1000 rpm to obtain a dispersion of the adhesive material, wherein the weight average molecular weight of polyvinylidene fluoride was 110,000.

[0111] Graphene oxide, oxidized activated carbon, and N-methylpyrrolidone were mixed in a mass ratio of 1:10:20 and stirred in a homogenizer at 25 °C for 3 hours at a stirring speed of 1000 rpm. Then, the mixture was mixed with the dispersion of the above binder material and stirred for another 5 hours at a stirring speed of 1000 rpm. The mixed slurry was filtered through a 200-mesh stainless steel mesh to obtain the electrode composition in this example.

[0112] In this example, the electrode composition contains 25% by mass of solids (solids refer to polyvinylidene fluoride, graphene oxide, and oxidized activated carbon). Of this, based on a total solids content of 100%, polyvinylidene fluoride comprises 6.3%, graphene oxide 8.5%, and oxidized activated carbon 85.2%. Specifically, the graphene oxide contains 1% oxygen by mass, and the oxidized activated carbon contains 8% oxygen by mass.

[0113] Example 4 This example provides an electrode composition, which is prepared by the following method, including the following steps: Sodium carboxymethyl cellulose was mixed with water at a mass ratio of 1:20 and dispersed by stirring at 25 °C for 3 hours using a homogenizer at a stirring speed of 1000 rpm to obtain a dispersion of the binder material, wherein the weight average molecular weight of sodium carboxymethyl cellulose was 80,000.

[0114] The conductive carbon black oxidized (which is oxidized using a modified Hammer process, in which the oxidizing agents are concentrated sulfuric acid and potassium permanganate with a mass fraction of 98%), the oxidized activated carbon, and water are mixed in a mass ratio of 1:10:20 and stirred in a homogenizer at 25 °C for 5 hours at a stirring speed of 1000 rpm. Then, it is mixed with the dispersion of the above-mentioned binder material and stirred for another 10 hours at a stirring speed of 1000 rpm. The mixed slurry is filtered through a stainless steel mesh with a mesh size of 200 to obtain the electrode composition in this example.

[0115] In this example, the electrode composition contains 25% by mass of solids (solids refer to sodium carboxymethyl cellulose, conductive carbon black oxide, and oxidized activated carbon). Specifically, based on the total mass percentage of solids in the electrode composition being 100%, sodium carboxymethyl cellulose accounts for 6.3%, conductive carbon black oxide accounts for 8.5%, and oxidized activated carbon oxide accounts for 85.2%. The conductive carbon black oxide contains 10% oxygen by mass, and the oxidized activated carbon oxide contains 2% oxygen by mass.

[0116] Example 5 This example provides an electrode composition, which is prepared by the following method, including the following steps: Polyacrylonitrile and acetonitrile were mixed at a mass ratio of 1:20 and dispersed by stirring at 25 °C for 3 hours using a homogenizer at a stirring speed of 1000 rpm to obtain a dispersion of the adhesive material, wherein the weight average molecular weight of the polyacrylonitrile was 2,000,000.

[0117] Carbon nanotubes (i.e., oxidized conductive carbon material), oxidized activated carbon (i.e., porous carbon material), and acetonitrile were mixed in a mass ratio of 1:7.5:10 and stirred in a homogenizer at 25 °C for 3 hours at a stirring speed of 1000 rpm. Then, the mixture was mixed with the dispersion of the above binder material and stirred for another 5 hours at a stirring speed of 1000 rpm. The mixed slurry was filtered through a 200-mesh stainless steel mesh to obtain the electrode composition in this example.

[0118] In this example, the electrode composition contains 31% by mass of solids (solids refer to polyacrylonitrile, carbon nanotubes, and oxidized activated carbon). Specifically, based on the total mass percentage of solids in the electrode composition being 100%, polyacrylonitrile accounts for 5.5%, carbon nanotubes for 11.2%, and oxidized activated carbon for 83.3%. The carbon nanotubes contain 1% oxygen by mass, and the oxidized activated carbon contains 8% oxygen by mass.

[0119] Example 6 This example provides an electrode composition, which is prepared by the following method, including the following steps: Polyacrylonitrile and acetonitrile were mixed at a mass ratio of 1:7 and dispersed by stirring at 25 °C for 3 hours using a homogenizer at a stirring speed of 1000 rpm to obtain a dispersion of the adhesive material, wherein the weight average molecular weight of the polyacrylonitrile was 2,000,000.

[0120] Carbon nanotubes (i.e., oxidized conductive carbon material), oxidized activated carbon (i.e., porous carbon material), and acetonitrile were mixed in a mass ratio of 1:7.5:10 and stirred in a homogenizer at 25 °C for 3 hours at a stirring speed of 1000 rpm. Then, the mixture was mixed with the dispersion of the above binder material and stirred for another 5 hours at a stirring speed of 1000 rpm. The mixed slurry was filtered through a 200-mesh stainless steel mesh to obtain the electrode composition in this example.

[0121] In this example, the electrode composition contains 40% solids (solids refer to polyacrylonitrile, carbon nanotubes, and oxidized activated carbon) by mass. Specifically, based on the total mass percentage of solids in the electrode composition being 100%, polyacrylonitrile accounts for 5.5%, carbon nanotubes for 11.2%, and oxidized activated carbon for 83.3%. The carbon nanotubes contain 10% oxygen by mass, and the oxidized activated carbon contains 8% oxygen by mass.

[0122] Example 7 This example provides an electrode composition, which is prepared by the following method, including the following steps: Polyacrylonitrile and acetonitrile were mixed at a mass ratio of 1:32 and dispersed by stirring at 25 °C for 3 hours using a homogenizer at a stirring speed of 1000 rpm to obtain a dispersion of the adhesive material, wherein the weight average molecular weight of the polyacrylonitrile was 2,000,000.

[0123] Carbon nanotubes (i.e., oxidized conductive carbon material), oxidized activated carbon (i.e., porous carbon material), and acetonitrile were mixed in a mass ratio of 1:12:20 and stirred in a homogenizer at 25 °C for 3 hours at a stirring speed of 1000 rpm. Then, the mixture was mixed with the dispersion of the above binder material and stirred for another 5 hours at a stirring speed of 1000 rpm. The mixed slurry was filtered through a 200-mesh stainless steel mesh to obtain the electrode composition in this example.

[0124] In this example, the electrode composition contains 21% by mass of solids (solids refer to polyacrylonitrile, carbon oxide nanotubes, and oxidized activated carbon). Specifically, based on the total mass percentage of solids in the electrode composition being 100%, the mass percentages of polyacrylonitrile, carbon oxide nanotubes, and oxidized activated carbon are 7.1%, 7.1%, and 85.8%, respectively. Furthermore, the carbon oxide nanotubes contain 10% oxygen by mass, and the oxidized activated carbon contains 8% oxygen by mass.

[0125] Example 8 This example provides a capacitive deionization electrode, which includes a substrate and an electrode layer attached to the substrate. The electrode layer is made using the electrode composition of Example 1.

[0126] The capacitive deionization electrode in this example was prepared using the following method, including the following steps: The electrode from Example 1 was coated onto a titanium foil with the composition and dried to obtain the capacitive deionization electrode of this example.

[0127] Example 9 This example provides a capacitive deionization electrode, which includes a substrate and an electrode layer attached to the substrate. The electrode layer is made using the electrode composition of Example 2.

[0128] The capacitive deionization electrode in this example was prepared using the following method, including the following steps: The electrode from Example 2 was coated onto a titanium foil with the composition and dried to obtain the capacitive deionization electrode of this example.

[0129] Example 10 This example provides a capacitive deionization electrode, which includes a substrate and an electrode layer attached to the substrate. The electrode layer is made using the electrode composition of Example 3.

[0130] The capacitive deionization electrode in this example was prepared using the following method, including the following steps: The electrode from Example 3 was coated onto a titanium foil with the composition and dried to obtain the capacitive deionization electrode of this example.

[0131] Example 11 This example provides a capacitive deionization electrode, which includes a substrate and an electrode layer attached to the substrate. The electrode layer is made using the electrode composition of Example 4.

[0132] The capacitive deionization electrode in this example was prepared using the following method, including the following steps: The electrode from Example 4 was coated onto a titanium foil with the composition and dried to obtain the capacitive deionization electrode of this example.

[0133] Example 12 This example provides a capacitive deionization electrode, which includes a substrate and an electrode layer attached to the substrate. The electrode layer is made using the electrode composition of Example 5.

[0134] The capacitive deionization electrode in this example was prepared using the following method, including the following steps: The electrode from Example 5 was coated onto a titanium foil with the composition and dried to obtain the capacitive deionization electrode of this example.

[0135] Example 13 This example provides a capacitive deionization electrode, which includes a substrate and an electrode layer attached to the substrate. The electrode layer is made using the electrode composition of Example 6.

[0136] The capacitive deionization electrode in this example was prepared using the following method, including the following steps: The electrode from Example 6 was coated onto a titanium foil with the composition and dried to obtain the capacitive deionization electrode of this example.

[0137] Example 14 This example provides a capacitive deionization electrode, which includes a substrate and an electrode layer attached to the substrate. The electrode layer is made using the electrode composition of Example 7.

[0138] The capacitive deionization electrode in this example was prepared using the following method, including the following steps: The electrode from Example 7 was coated onto a titanium foil with the composition and dried to obtain the capacitive deionization electrode of this example.

[0139] Example 15 This example provides a water purifier, and the electrode of the water purifier in this example adopts the capacitive deionization electrode of Example 8.

[0140] Example 16 This example provides a water purifier, and the electrode of the water purifier in this example adopts the capacitive deionization electrode of Example 9.

[0141] Example 17 This example provides a water purifier, and the electrode of the water purifier in this example adopts the capacitive deionization electrode of Example 10.

[0142] Example 18 This example provides a water purifier, and the electrode of the water purifier in this example adopts the capacitive deionization electrode of Example 11.

[0143] Example 19 This example provides a water purifier, and the electrode of the water purifier in this example adopts the capacitive deionization electrode of Example 12.

[0144] Example 20 This example provides a water purifier, and the electrode of the water purifier in this example adopts the capacitive deionization electrode of Example 13.

[0145] Example 21 This example provides a water purifier, and the electrode of the water purifier in this example adopts the capacitive deionization electrode of Example 14.

[0146] Performance testing: (1) Surface morphology test The surface morphology of the capacitive deionization electrode in Example 8 was tested using scanning electron microscopy. The specific test method is as follows: Figure 1 As shown, by Figure 1 It can be seen that the capacitive deionization electrode in Example 8 has a loose and porous surface morphology, with pore size distribution mainly at the micrometer level. This allows for unrestricted mass transfer and diffusion of hydrated ions, enabling them to pass quickly and efficiently through the pores on the surface of the capacitive deionization electrode and subsequently adsorb inside, thus achieving desalination. Furthermore, from... Figure 1 It can also be seen that the oxidized activated carbon and carbon oxide nanotubes are entangled together, and the oxidized activated carbon is uniformly dispersed without agglomeration. The reason is that both the oxidized activated carbon and carbon oxide nanotubes have oxygen-containing functional groups distributed on their surfaces. These oxygen-containing functional groups form hydrogen bonds, thereby connecting the oxidized activated carbon and carbon oxide nanotubes. In addition, carbon oxide nanotubes and oxidized activated carbon can also be physically entangled. Through chemical and physical entanglement, the oxidized activated carbon can be uniformly dispersed, preventing the granular oxidized activated carbon from agglomerating due to electrostatic effects, which would affect the uniformity of the surface composition and conductivity of the capacitor deion electrode.

[0147] (2) TDS test The capacitive deionization electrode from Example 8 was placed in a NaCl solution with a flow rate of 200 mL / min and a concentration of 200 mg / L. A working voltage of 1.5 V was then applied to test its desalination performance. The desalination rate was calculated using the formula: Desalination rate % = (Influent concentration - Effluent concentration) / Original influent concentration × 100%. The adsorption rate was calculated using the formula: Adsorption rate = (Desalination rate × Influent concentration × Flow rate) / Electrode area. The TDS and voltage relationship curves for the desalination performance test of the capacitive deionization electrode from Example 8 are shown below. Figure 2 As shown. By Figure 2 It can be seen that the capacitive deionization electrode in Example 8 achieved a desalination rate of 86.1% after 2 minutes of use, and the maximum adsorption rate was 323 mg / (m²). 2 ·min).

[0148] The capacitive deionization electrode from Example 9 was placed in a NaCl solution with a flow rate of 200 mL / min and a concentration of 200 mg / L. A working voltage of 2 V was then applied to test its desalination performance. The desalination rate was calculated using the formula: Desalination rate % = (Influent concentration - Effluent concentration) / Original influent concentration × 100%. The adsorption rate was calculated using the formula: Adsorption rate = (Desalination rate × Influent concentration × Flow rate) / Electrode area. The TDS and voltage relationship curves for the desalination performance test of the capacitive deionization electrode from Example 9 are shown below. Figure 3 As shown. By Figure 3 It can be seen that the capacitive deionization electrode in Example 9 achieved a desalination rate of 64.5% after 5 minutes of use, and the maximum adsorption rate was 241 mg / (m²). 2 ·min).

[0149] (2) Specific surface area, pore volume and resistivity test The specific surface area and pore volume (i.e., pore volume) of the capacitive deionization electrodes in Examples 8 and 9 were tested according to the test method described in GB / T 19587-2017 "Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method". Then, the AC impedance test data of the capacitive deionization electrodes in Examples 8 and 9 were tested using the four-probe method. The specific test results are shown in Table 1 below.

[0150] Table 1. Test results of specific surface area, pore volume and resistivity

[0151] As shown in Table 1, the capacitive deionization electrodes in Examples 8-9 of this invention all have a large specific surface area (987-1106 m²). 2 / g), with a relatively high pore volume (0.84~1.06 cm³). 3 With its low resistivity (0.32~0.64Ω·cm), it meets the requirements for use as a capacitive deionization electrode.

[0152] Tests revealed that the performance of the capacitive deionization electrodes in Examples 10-14 was basically equivalent to that in Examples 8 and 9.

[0153] In summary, by introducing an oxidized conductive carbon material with excellent conductivity into oxidized activated carbon, this invention can improve the overall conductivity of the capacitive deionization electrode, reduce the resistivity of the capacitive deionization electrode to 0.3~0.7Ω·cm, and enable rapid charge transfer within the electrode, thereby increasing the desalination rate of the electrode.

[0154] Furthermore, the oxidized conductive carbon material and the oxidized activated carbon are connected through hydrogen bonds and physical entanglement, preventing the oxidized activated carbon from agglomerating due to electrostatic effects and improving its dispersibility. This reduces the amount of binder used during electrode preparation, ensuring it does not exceed 10%. Since binders are generally non-conductive, excessive binder usage can affect the electrode's conductivity. Conversely, insufficient binder usage can lead to the shedding of the oxidized conductive carbon material and porous carbon material during electrode preparation, impacting electrode lifespan and desalination rate. This invention, through physical and chemical entanglement between the oxidized activated carbon and the oxidized conductive carbon material, prevents the shedding of these materials while reducing binder usage.

[0155] The capacitive deionization electrode of this invention has a micron-sized pore size, which allows for unrestricted mass transfer and diffusion of hydrated ions. The electrode also has a large specific surface area (700~2500 m²). 2 / g), relatively large pore volume (0.8~1.1 cm³). 3 / g), which has a large contact area with salt during desalination, improves the desalination rate and effect, and enables the maximum adsorption rate of anions and cations to reach 240~330 mg / (m 2 (min), the desalination rate is not less than 60% when the working voltage is 1.5~2V.

[0156] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A capacitive deionization electrode, characterized in that: The electrode includes an electrode layer; the raw material for preparing the electrode layer is an electrode composition; the electrode composition includes a porous carbon material, an oxidized conductive carbon material, and a binder, wherein the mass ratio of the binder, the porous carbon material, and the oxidized conductive carbon material is 1:(10~16):(0.8~2.5); the specific surface area of ​​the capacitive deionization electrode is 700~2500 m². 2 / g, pore volume 0.8~1.1 cm³ 3 / g, resistivity 0.3~0.7Ω·cm; The electrode composition contains at least a portion of the porous carbon material and the oxidized conductive carbon material connected by hydrogen bonds and / or physical entanglement; The porous carbon material is oxidized activated carbon, and the mass percentage of oxygen in the oxidized activated carbon is 1-10%. The oxygen mass percentage in the oxidized conductive carbon material is 1-30%.

2. The capacitive deionization electrode according to claim 1, characterized in that: The conductive carbon material is selected from at least one of graphene, carbon nanotubes, conductive carbon black, and carbon fiber.

3. The capacitive deionization electrode according to claim 1, characterized in that: The porous carbon material is granular; the conductive carbon material is selected from carbon nanotubes, carbon fibers, or combinations thereof.

4. The capacitive deionization electrode according to claim 1, characterized in that: The electrode composition further includes a solvent; the solvent has a mass percentage of 60-95% based on 100% of the electrode composition by mass.

5. The capacitive deionization electrode according to claim 4, characterized in that: The solvent is selected from at least one of methanol, ethanol, ethylene glycol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, carbon tetrachloride, N-methylpyrrolidone, and water.

6. The capacitive deionization electrode according to claim 1, characterized in that: The adhesive is selected from at least one of polyacrylic acid, polyethylene glycol, polyvinyl alcohol, polyamic acid, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, carboxymethyl cellulose, sodium hydroxymethyl cellulose, and styrene-butadiene rubber.

7. The capacitive deionization electrode according to claim 1, characterized in that: The weight-average molecular weight of the adhesive is 5,000 to 2,000,000.

8. The capacitive deionization electrode according to claim 1, characterized in that: The electrode composition is prepared by a method comprising the following steps: mixing the oxidized conductive carbon material, the porous carbon material, the binder, and optionally added solvent.

9. The capacitive deionization electrode according to claim 1, characterized in that: The electrode composition is prepared by a method comprising the following steps: S1: The binder is mixed with a portion of the solvent to obtain a binder dispersion; the oxidized conductive carbon material, the porous carbon material, and the remaining solvent are mixed to obtain a conductive dispersion; S2: The binder dispersion and the conductive dispersion are mixed to obtain the electrode composition.

10. The capacitive deionization electrode according to any one of claims 1-9, characterized in that: The capacitive deionization electrode has at least one of the following characteristics: (a) The maximum adsorption rate of anions and cations is 200~400 mg / (m 2 ·min); (b) The desalination rate of the capacitor deionization electrode at a working voltage of 1.5~2V is not less than 60%.

11. A water treatment device, characterized in that: Includes the capacitive deionization electrode according to any one of claims 1 to 10.

12. The water treatment equipment according to claim 11, characterized in that: The water treatment equipment includes water purification equipment, water desalination equipment, and water softening equipment.

13. The application of the capacitive deionization electrode according to any one of claims 1 to 10 in the field of water treatment.

Citation Information

Patent Citations

  • Preparation method of porous carbon electrode

    CN106783212A

  • Asymmetric CDI desalination module and method for desalination by using same

    CN111732165A

  • KR20220041491A